When a Slice Is Not Enough! Comparison of Whole-Brain versus Standard Limited-Slice Perfusion Computed Tomography in Patients with Severe Traumatic Brain Injury - Cooper, Shannon (J Clin Med, 2019)
Introduction: Cerebral perfusion computed tomography (PCT) provides crucial information in acute stroke and has an increasing role in traumatic brain injury (TBI) management. Most studies on TBI patients utilize 64-slice scanners, which are limited to four brain slices (limited-brain PCT, LBPCT). Newer 320-slice scanners depict the whole brain perfusion status (WBPCT). We aimed to identify the additional information gained with WBPCT when compared to LBPCT. Patients and methods: Forty-nine patients with severe TBI were investigated within 48 h from admission with WBPCT. Findings from LBPCT were compared with findings from WBPCT. Results: A perfusion abnormality was identified in 39 (80%) and 37 (76%) patients by WBPCT and LBPCT, respectively (p = 0.8). There were 90 and 68 perfusion abnormalities identified by WBPCT and LBPCT, respectively (p < 0.001). In the 39 patients with a perfusion abnormality detected by WBPCT, 15 (38%) had further perfusion abnormalities outside the LBPCT area of coverage. Thirty-six (92%) patients had a larger perfusion abnormality upon WBPCT compared with LBPCT. Additional information gained showed some statistically significant correlation with clinical outcome. Conclusions: In severe TBI patients, WBPCT provides extra information compared to LBPC. The limitations of LBPCT should be considered when evaluating studies reporting on PCT findings and their association with outcomes.